High strain rate behavior of graphene-epoxy nanocomposites - Colak, Ozgen U.; Bahlouli, Nadia; Uzunsoy, Deniz; Francart, Charles (ELSEVIER SCI LTD, 2020)
This work consists of the synthesis of high purity graphene nanoflakes (GNF), the manufacturing of GNF-epoxy nanocomposites and the mechanical characterization of the nanocomposite at high and quasi static strain rates, (2750/s - 1.E 5/s). GNF were synthesized by using the electric arc discharge technique. Thermogravimetry/ Differential Thermal Analysis (TG/DTA) of synthesized graphene reveals high purity and high crystallinity. Raman spectra and the broad Brunauer-Emmet-Teller (BET) specific surface area indicate that the synthesized graphene has several layers. Following the solution mixing manufacturing process of GNF-epoxy nanocomposites, the influences of strain rate on the mechanical behaviors are investigated under quasi static and dynamic loadings. High strain rate uniaxial compression tests (1270-2750/s) using Split Hopkinson Pressure Bar (SHPB) and quasi static compression tests (1.E-3 and 1.E-5/s) of GNF-epoxy with two graphene contents (0.1 and 0.5 wt %) are performed at room temperature. The maximum elasticity modulus achieved by the GNF-epoxy with 0.5 wt% at the strain rate of 2350/s corresponds to a 68% increase compared to the neat epoxy. The yield strength of the material is doubled under dynamic loading conditions compared to the quasi static loading.
Keywords: Graphene-epoxy nanocomposite; Split hopkinson bar; Compression test; Electric arc discharge technique; MECHANICAL-PROPERTIES; ARC-DISCHARGE; DEFORMATION; Materials Science; Polymer Science